2021
DOI: 10.3389/fmicb.2021.602653
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Diversity and Pathogenic Potential of Clinical and Environmental Vibrio parahaemolyticus Isolates From Brazil

Abstract: Vibrio parahaemolyticus strains recovered from human diarrheal stools (one in 1975 and two in 2001) and environmental sources (four, between 2008 and 2010) were investigated for the presence of virulence genes (trh, tdh, and vpadF), pandemic markers (orf8, toxRSnew), and with respect to their pathogenic potential in two systemic infection models. Based only on the presence or absence of these genetic markers, they were classified as follows: the environmental strains were non-pathogenic, whereas among the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 95 publications
(140 reference statements)
0
7
0
Order By: Relevance
“…For example, Xu and colleagues (2015) reported that 14% of clinical isolates harbored neither genes, that is, these strains would conventionally be classified as avirulent [ 42 ]. Even though hemolysins alone can cause symptoms on the host, other virulence factors may play an important role, such as proteases, siderophores, biofilm-forming ability, and secretion systems [ 40 , 42 , 43 , 44 ]. It is also worth mentioning that the pathogenic potential of Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xu and colleagues (2015) reported that 14% of clinical isolates harbored neither genes, that is, these strains would conventionally be classified as avirulent [ 42 ]. Even though hemolysins alone can cause symptoms on the host, other virulence factors may play an important role, such as proteases, siderophores, biofilm-forming ability, and secretion systems [ 40 , 42 , 43 , 44 ]. It is also worth mentioning that the pathogenic potential of Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…(Ramos et al, 2012) Oyster V. parahaemolyticus and V. vulnificus (ND) Florianópolis, SC (Ramos et al, 2014) Oyster V. parahaemolyticus (35%), V. vulnificus (10%), V. alginolyticus (7%) and V. fluvialis (2%) Mollusc farming water V. parahaemolyticus (45%), V. alginolyticus (29%) and V. vulnificus (13%) Florianópolis, SC (Silva et al, 2016a) Oyster and mussel V. parahaemolyticus (~ 11%) Shellfish farming water V. parahaemolyticus (18%) Lagoa dos Patos, RS (Rosa et al, 2016) Fish V. parahaemolyticus (<1%) Lagoa dos Patos, RS (Rosa et al, 2017) Fish V. parahaemolyticus (3.3%) Lagoa dos Patos, RS (Silveira et al, 2019) Fish Vibrio spp. (68%) and V. vulnificus (0.01%) Southeast region Rio de Janeiro, RJ (Oliva et al, 2016) Mussel V. parahaemolyticus (44.7%), V. alginolyticus (19.6%) and V. vulnificus (12.4%) Rio de Janeiro, RJ (Bouzas, 2021) Mussel V. parahaemolyticus (ND) Rio de Janeiro (Santos et al, 2021) Oyster farm V. parahaemolyticus (ND) Northeast region Baía de Todos os Santos, BA (Rodrigues & Carvalho, 2011) Oyster V. parahaemolyticus (ND)…”
Section: Discussionmentioning
confidence: 99%
“…All primer sequences and amplification conditions were taken from their respective references ( Table S2 ). Genomic DNA from strains of Vibrio parahaemolyticus IOC 17381 ( toxR + and tdh + ) and 0798081 ( trh + ) were used as positive controls for the respective virulence genes targeted by PCR [ 35 ]. Amplicons were observed through 1–2% agarose gel electrophoresis using the Low DNA Mass Ladder (Thermo Fisher Scientific, Waltham, MA, USA) as the molecular size standard.…”
Section: Methodsmentioning
confidence: 99%